PENGAWASAN PENGELOLAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL KOTA MANADO - FATMAWATI, DIANA; RARES, JOYCE JACINTA; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2018)
ABSTRACT: Supervision of the management of the charity that is evaluating the implementation of thepolicy of the management of zakat refers to national legislation, regulations or guidelines issued by BadanAmil Zakat Nasional the supervisory function has an important role in the management and the collectionof tithes in the amil zakat nasional can become an opportunity and also a threat to the national body of amilzakat.This research aims to find out the supervision management of zakat in the amil zakat nasional cityof Manado. This study uses qualitative methods. Informants in this study amounted to 7 peoples. Thetechnique used is the data collection guidelines for interviews and assisted with interviews and observation.Measurement using the theory of Terry with 4 indicator measurement supervision supervisory standard,measuring the implementation of activities, comparing the standard of supervision with the results of theactivities, the act of correction.The results of this study claimed that using 4 measurement indicators in the supervision ofmanagement of zakat in the amil zakat nasional of the city Manado votes are enough runs well but thegovernment should be more responsive in the form of budget funds against the management of zakat inorder to ease the National agencies Amil Zakat Manado can perform its activities effectively and efficiently.Thus, it can be concluded when the supervision management of zakat in the amil zakat national in Manadohas been running quite effectively. Advice agency supervisor at least better understand and apply the returnto law No. 23 year 2011 about the management of zakat, Enhance socialization about the charity so that thecommunity could be more active in channelling zakat to receive zakat compulsory in accordance with thetargets that scroll.Keywords: Supervision, of the management zakat